Non-melanoma skin cancer among ethnic German immigrants (resettler) from the former Soviet Union: a cohort study from 1990 to 2007 - Evgenia Markeeva-Ilisevic; Bernd Holleczek; Heiko Becher; Volker Winkler (BMC, 2022)
Abstract Background UV radiation is a significant risk factor for non-melanoma skin cancer (NMSC). Ethnic Germans (resettlers) who immigrated to Germany from the former Soviet Union may have had a relatively high UV light exposure and thus a higher risk of developing NMSC. We compared the incidence of NMSC in a resettler cohort with the general population of the Saarland (Federal state of Germany) in relation to tumour location. Methods All new NMSC cases (resettler cohort and total population) between 1990 and 2007 were retrieved from the Saarland cancer registry and classified according to sex, histology, and location. The classification used for tumour location approximated the previous UV exposure. Age-standardized incidence rates (ASR) for the general population and standardized incidence ratios (SIR) for resettlers compared to the general population were calculated and modelled using Poisson regression. Results Sex-specific overall SIR indicated a significant increase in female resettlers (SIR 1.31 (95% CI 1.02-1.67)) which can mostly be attributed to an increased incidence of squamous cell carcinoma. The regression analysis showed that among resettlers the risk of developing tumours in UV-exposed skin areas was 2.16 (95% CI 1.35-3.45) higher compared to the general population. Conclusions Female resettlers have a higher risk to be diagnosed with NMSC than the general German population. Based on the observed distribution of tumour location, it is suspected that UV exposure contributed significantly to this risk.